Intracellular construction of topology-controlled polypeptide nanostructures with diverse biological functions. Issue 1 (December 2017) - Li, Li-Li; Qiao, Sheng-Lin; Liu, Wei-Jiao; Ma, Yang; Wan, Dong; Pan, Jie; Wang, Hao
Abstract Topological structures of bio-architectonics and bio-interfaces play major roles in maintaining the normal functions of organs, tissues, extracellular matrix, and cells. In-depth understanding of natural self-assembly mechanisms and mimicking functional structures provide us opportunities to artificially control the natural assemblies and their biofunctions. Here, we report an intracellular enzyme-catalyzed polymerization approach for efficient synthesis of polypeptides and in situ construction of topology-controlled nanostructures. We reveal that the phase behavior and topological structure of polypeptides are encoded in monomeric peptide sequences. Next, we elucidate the relationship between polymerization dynamics and their temperature-dependent topological transition in biological conditions. Importantly, the linearly grown elastin-like polypeptides are biocompatible and aggregate into nanoparticles that exhibit significant molecular accumulation and retention effects. However, 3D gel-like structures with thermo-induced multi-directional traction interfere with cellular fates. These findings allow us to exploit new nanomaterials in living subjects for biomedical applications. The intracellular topology of a nanostructure plays a major role in its interactions with the cell and accordingly, its biological applications. Here, the authors design peptides that intracellularly polymerize into elastin-like polypeptides and assemble into various topologies, each of which exhibits a distinct set of biological functions.